Arabic Language Learning Progress in Darussakinah Batu Bersurat Islamic Boarding School - Muhammad Azhar; Hakmi Wahyudi; Promadi Karim; Jon Pamil (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to explore and investigate Arabic and grammar learning at the Darussakinah Batu Bersurat Islamic Boarding School from 2005 to 2017 and from 2018 to now and to compare aspects of progress in learning Arabic from the two periods. The method used is the descriptive qualitative method, with data collection techniques through interviews, observation, and documentation. The results of this study indicate that the progress of learning Arabic at the Darussakinah Batu Bersurat Islamic Boarding School is contained in several aspects; namely, aspects of the purpose of Arabic learning objectives, the textbooks used, the learning process, and the learning methods used. The purpose of learning Arabic at the Darussakinah Batu Bersurat Islamic Boarding School today is receptive and expressive. The Arabic language textbook uses the target language to accelerate language acquisition. The language of the Arabic grammar textbook uses the students' mother tongue so that Arabic grammar learning is effective and efficient. Teachers use varied learning methods to make learning not boring. The process of learning Arabic grammar in this Islamic boarding school is theoretically applicable by analyzing Arabic texts with the theories studied. Learning like this makes students understand and feel the benefits of learning grammar. The Arabic language learning process emphasizes more aspects of oral and written communication so that students feel the meaning of their lives from the learning carried out; with this meaning, students are active and enthusiastic about learning Arabic.